Learning to Set Prices - Huang, Yufeng; Ellickson, Paul B.; Lovett, Mitchell J. (Journal of Marketing Research, 2022)
The authors empirically examine how firms learn to set prices in a new market. The 2012 privatization of off-premises liquor sales in Washington State created a unique opportunity to observe retailers learning to set prices from the beginning of the learning process. Tracking this market as it evolved through time, the authors find that firms indeed learn to set more profitable prices, that these prices increasingly reflect demand fundamentals, and that prices ultimately converge to levels consistent with (static) profit maximization. The authors further demonstrate that initial pricing mistakes are largest for products whose demand conditions differ the most from those of previously privatized markets, that retailers with previous experience in the category are initially better informed, and that learning is faster for products with more precise sales information. These findings indicate that firm behavior converges to rational models of firm conduct, but such convergence takes time to unfold and plays out differently for different firms. These patterns suggest the important roles of firms’ learning and heterogeneous firm capabilities.